Cover, Table of Contents, and Editorial Note – Vol. 14 No. 1 (2025) - Ahmad Mukhlasin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This file contains the journal cover, table of contents, and the editorial note from the Editor in Chief for Volume 14, Issue 1 (2025). These components serve as the opening elements of the journal edition and reflect the overarching theme and editorial perspective of this issue.